PENGARUH PEMBERIAN AIR REBUSAN DAUN SIRIH TERHADAP KEPUTIHAN PADA WANITA PASANGAN USIA SUBUR DI WILAYAH KERJA KLINIK MANDING KABUPATEN POLEWALI MANDAR - Hadriyani Amin; Ummu Kalsum; Sahrir Ramadhan (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Leucorrhoea (Flour Albus) is excessive discharge from the birth canal or vagina. Normal vaginal discharge occurs in women, which occurs before and after the fertile period. According to WHO (World Health Organization) the number of women in the world in 2013 was 6.7 billion people and those who had experienced vaginal discharge were around 75%, while European women in 2013 were 739,004,470 people and those who had vaginal discharge were 25%. In Indonesia, about 90% of women have the potential to experience vaginal discharge because the country of Indonesia is a tropical climate, so mushrooms are easy to grow and develop which results in many cases of vaginal discharge in Indonesian women. The method used in this study is EkprerimentalQuasywith pre and post test without control research plans. Sampling using the Total Sampling technique and obtained 17 Respondents in accordance with the Inclusion criteria, Data collection was carried out using observation sheets. Observation was carried out before and after being given betel leaf stew water. The collected data is then processed using a T-test. P-value was obtained after giving betel leaf boiled water which is 0,000. The conclusion in this study is the provision of betel leaf boiled water affects the treatment of vaginal discharge in women of childbearing age in the Manding clinic